Croton palanostigma (sangre de grado) latex-induced gastric juice peptic activity stimulation - Sandoval, Miguel (2008)
Objective: To determine if Croton palanostigma (sangre de grado) oral administration modifies gastric secretion peptic activity. Design: Experimental study. Institution: Alberto Guzman Barron Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Biologic material: Adult male albino rats and sangre de grado. Methods: Fifty 200 to 250 g adult male albino rats were randomly distributed in 5 groups according to sangre de grado oro-gastric one dose administration: group I: 0,8 mL/kg of sangre de grado; group II: 0,8 mL/kg of neutralized sangre de grado; group III: ranitidine 50 mg/kg; group IV: control group with saline solution 0,9 g% (without histamine); group V: control group with saline solution 0,9 g%. Pyloric ligature by laparotomy was done under ethylic ether anesthesia. Subcutaneously applied histamine was used to stimulate secretion, except to group IV. Four hours later, gastric juice was extracted, volume was measured, pH was determined by potentiometry and pepsin activity by modified Anson method, measured as tirosine μg/mL. Main outcome measures: Gastric secretion peptic activity modification. Results: Gastric juice volume was significantly lower in groups II and III, with no statistic difference in the other groups. Group III pH (with ranitidine) was significantly higher, showing the medicine effect. Peptic activity was as follows: 5,34+1,04 with sangre de grado; 2,69+1,27 with neutralized sangre de grado; 2,57+0,88 the ranitidine group; 3,29+0,94 control group without histamine and 3,58+1,18 control group with histamine. Peptic activity was significantly higher (+49,2%) in the sangre de grado group (p<0,01). Conclusions: There was gastic peptic activity following the oro-gastric administration of Croton palanostigma (sangre de grado), with no pH variation.